Muscle deterioration due to rheumatoid arthritis: assessment by quantitative MRI and strength testing. (10th September 2020) - Farrow, Matthew; Biglands, John; Tanner, Steven; Hensor, Elizabeth M A; Buch, Maya H; Emery, Paul; Tan, Ai Lyn
Abstract: Objectives: RA patients often present with low muscle mass and decreased strength. Quantitative MRI offers a non-invasive measurement of muscle status. This study assessed whether MRI-based measurements of T2, fat fraction, diffusion tensor imaging and muscle volume can detect differences between the thigh muscles of RA patients and healthy controls, and assessed the muscle phenotype of different disease stages. Methods: Thirty-nine RA patients (13 'new RA'—newly diagnosed, treatment naïve, 13 'active RA'—persistent DAS28 >3.2 for >1 year, 13 'remission RA'—persistent DAS28 <2.6 for >1 year) and 13 age and gender directly matched healthy controls had an MRI scan of their dominant thigh. All participants had knee extension and flexion torque and grip strength measured. Results: MRI T2 and fat fraction were higher in the three groups of RA patients compared with healthy controls in the thigh muscles. There were no clinically meaningful differences in the mean diffusivity. The muscle volume, handgrip strength, knee extension and flexion were lower in all three groups of RA patients compared with healthy controls. Conclusion: Quantitative MRI and muscle strength measurements can potentially detect differences within the muscles between RA patients and healthy controls. These differences may be seen in RA patients who are yet to start treatment, those with persistent active disease, and those who were in clinical remission. This suggests that the muscles in RA patients are affected in the early stages of the disease and that signs of muscle pathology and muscle weakness are still observed in clinical remission.